The Analysis of Fiscal Policy and Fertility in Regency and City Governments in Indonesia - Khamilah Siregar, Oktarini; Karimi, Syafruddin; Indrawari, Indrawari; Ridwan, Endrizal (Opción, 2019)
This research aims to analyze whether fiscal policy affects fertility in Regency and City Governments Indonesia using panel data covering the time frame from 2007 to 2017, a cross-section of 432 regency and city governments in In- donesia. Increases in regional expenditure, regional debt, and regional budget deficits affect fertility decisions during the business cycle. However, region- al deficit is due to the high fertility in 432 regency and city governments in Indonesia. Households feel immoral to increase child demand as long as the provincial government is highly in debt and deficit due to low regional income. They do not want to burden future debt to their children and avoid sustaina- ble regional fiscal deficits.